More than Meets the Eye: The Aryl Hydrocarbon Receptor is an Environmental Sensor, Physiological Regulator and a Therapeutic Target in Ocular Disease - Hammond, Christine L.; Roztocil, Elisa; Gupta, Vardaan; Feldon, Steven E.; Woeller, Collynn F. (Frontiers in Toxicology, 2022)
The aryl hydrocarbon receptor (AHR) is a ligand activated transcription factor originally identified as an environmental sensor of xenobiotic chemicals. However, studies have revealed that the AHR regulates crucial aspects of cell growth and metabolism, development and the immune system. The importance of the AHR and AHR signaling in eye development, toxicology and disease is now being uncovered. The AHR is expressed in many ocular tissues including the retina, choroid, cornea and the orbit. A significant role for the AHR in age-related macular degeneration (AMD), autoimmune uveitis, and other ocular diseases has been identified. Ligands for the AHR are structurally diverse organic molecules from exogenous and endogenous sources. Natural AHR ligands include metabolites of tryptophan and byproducts of the microbiome. Xenobiotic AHR ligands include persistent environmental pollutants such as dioxins, benzo[a]pyrene (B[a]P) and polychlorinated biphenyls (PCBs). Pharmaceutical agents including the proton pump inhibitors, esomeprazole and lansoprazole, and the immunosuppressive drug, leflunomide, activate the AHR. In this review, we highlight the role of the AHR in the eye and discuss how AHR signaling is involved in responding to endogenous and environmental stimuli. We also present the emerging concept that the AHR is a promising therapeutic target for eye disease.